Destins tracés et contraction des horizons : être chômeuse au Portugal - Pedro Araujo (Genre, Sexualité et Société)
Based on the study of unemployment experiences of female ex-workers in a ceramics factory in Coimbra (Centre Region of Portugal), that went bankrupted in 2001, this article consists of two main parts. The first part discusses the outline of the analytic grid used in the qualitative research to understand unemployment experiences, and presents some of the main results obtained. The second part highlights the unemployment lived experiences of two women - Teresa and Andreia. It is argued that for unemployed older women in Portugal two main trends emerge: traced destinies, which express themselves through a higher investment in the private sphere; and, foreclosed futures, visible by a sharp reduction in the possible professional options available. These are two trends that, although always present in the Portuguese social configuration and in the labour market organisation, are also relevant to women’s unemployment experiences.